Impact of agroforestry trees on biomass production, carbon sequestration and soil properties on degraded lands in the Himalayan foothills - Megha, V R; Rjesh Kaushal (Guide) (Vellanikkara College of Climate Change and Environmental Science, 2024)
Agroforestry, a sustainable land management strategy, mitigates climate change by sequestering carbon (C) and producing biomass. This study on an 11-year-old Bauhinia variegata and Celtis australis plantation in the Himalayan foothills employed a destructive method to investigate biomass production and C sequestration in agroforestry systems. Diameter at breast height (DBH), Height, D2H, and D-H were used in developing allometric models. Models, especially those based on DBH, showed strong predictive power for estimating biomass components in both B. variegata and C. australis. The adjusted Rp2 (Bfor the allometric models ranged from 0.8 to 0.9, indicating high goodness-of-fit and improved efficiency in biomass estimates. Cross-validation confirmed model stability, making them reliable for biomass prediction. Non-significant t values (p > 0.05) validated the model. Using the models, total above ground biomass (AGB) ranged from 42.02 to 54.83 Mg ha-1, root biomass from 9.37 to 10.84 Mg ha-1, and total tree biomass from 51.39 to 65.67 Mg ha-1. Annual biomass increments were 4.67 Mg ha-1 yr-1 for C. australis and 5.97 Mg ha-1 yr-1 for B. variegata. B. variegata exceeds C. australis in C sequestration and stock, as shown by non-destructive analysis of biomass distribution and growth. Stored C (bole + branch + root) for both species ranged from 22.38 to 28.86 Mg ha-1, with total C stock from 23.80 to 30.47 Mg C ha-1. C sequestration in C. australis and B. variegata was 82.11 and 105.93 Mg ha-1, respectively, with net oxygen release between 59.72 and 77.04 Mg ha-1. Soil analysis shows improved aggregation, lower density in plantations, notably with B. variegata. Both species enhance soil microbes variably. C. australis improves soil quality with enhancing NPK, soil organic carbon, and C stock. The study underscores agroforestry's role in land restoration, biomass production, C capture, soil health, and sustainable land management in the Himalayass
MSc.
Keywords: Climate Change and Environmental Science; Agroforestry trees; Biomass production and carbon sequestration; Himalayan foothills